Magnetic sol-gel derived poly(oxyethylene)-siloxane nanohybrids - Amaral, V. S.; Carlos, L. D.; Silva, N. J O; De Zea Bermudez, V.; Dahmouche, K. [UNESP]; Santilli, Celso Valentim [UNESP]; Craievich, A. F.; Palacio, F. (Springer Nature, 2002)
The magnetic and structural properties of sol-gel derived organic/inorganic nanocomposites doped with Fe(II), Fe(III), Nd(III) and Eu (III) ions are discussed. These hybrids consist of poly(oxyethylene)-based chains grafted onto siloxane nanodomains by urea cross-linkages. Small angle X-ray scattering data show the presence of spatial correlations of siloxane domains embedded in the polymer matrix. The magnetic properties of rare-earth doped samples are determined by single ion crystal-field-splitted levels (Eu3+ J=0; Nd3+ J=9/2) and the small thermal irreversibility is mainly associated to structural effects. Fe2+ -doped samples behave as simple paramagnet with residual antiferromagnetic interactions. Fe3+-doped hybrids are much more complex, with magnetic hysterisis, exchange anisotropy and thermal irreversibility at low temperatures. Néel temperatures increase up to 14K for the highest (∼5.5%) Fe3+ mass concentration.
Keywords: Antiferromagnetism; Crosslinking; Doping (additives); Magnetic anisotropy; Magnetic hysteresis; Paramagnetic materials; Polyethylene glycols; Sol-gels; X ray scattering; Nanohybrid materials; Nanostructured materials